Providing Of Mahkota Dewa Fruit Extract (Phaleria Macrocarpa) To Reduce Malondialdehyde Levels In The Blood Of White Rats (Rattus Norvegicus) Triggered By Excessive Physical Activity - Restoe Agustin Riagara; Janice Janice; Bungaran Sihombing (International Journal of Health and Pharmaceutical (IJHP), 2023)
Anti-inflammatory, antioxidant, and apoptosis-modulating potential are just a few biological activities that have garnered much interest in natural food-derived components during the past two decades. Mahkota Dewa fruit (Phaleria macrocarpa) has several beneficial pharmacological activities. This study investigated whether Mahkota Dewa fruit extract (Phaleria macrocarpa) reduced malondialdehyde levels in blood samples of white rats (Rattus norvegicus) generated by excessive physical activity. The samples for this study were white rats (Rattus norvegicus) weighing 160-200 gr and 2-3 months old. The independent variable was the Mahkota Dewa fruit extract (Phaleria macrocarpa). The dependent variable was excessive physical activity-induced malondialdehyde levels in white rats (Rattus norvegicus). The average Malondialdehyde (MDA) levels show that the group given 5 ml of the Mahkota Dewa fruit extract (Phaleria macrocarpa) had tremendous success in lowering MDA levels compared to the other groups. The results of the observations and data analysis show that administration of the extract can reduce MDA levels significantly in male Wistar rats (Rattus norvegicus) because of too much exercise.